The incredibles Quezon City Residents' assessment of the credibility of local broadsheets and primetime TV news programs - Ramos, Regine Anne G.; Tanglao, Kessica Camille C.; Tatad, Rowena S.; Vasquez, Mariedel M. (2008)
The study explores two kinds of media credibility ? in terms of source and media forms - by determining the public's perception of the credibility of 1) specific media news sources; and 2) broadsheets and TV news programs in general. The sample consists of 112 Quezon City residents 18 years old and above who were selected using systematic random sampling. Results show that for newspapers, the Philippine Daily Inquirer and the Philippine Star were perceived to be equally credible, and that they were also seen as more credible than Manila Bulletin. For evening news programs, meanwhile, 24 Oras was seen as more credible than TV Patrol. In general, both broadsheets and TV news programs were seen as equally credible by the respondents. There were generally no significant differences in media credibility ratings across respondent groupings according to age and educational attainment; only older respondents and respondents with less education saw TV news programs as more credible than broadsheets.